Impact of COVID-19 on People with Disabilities - Pant , Smriti; Koirala , Saugat; Subedi, Madhusudan (Europasian Journal of Medical Sciences, 2021)
Any condition of the body or mind that makes it more difficult for the person with the condition to do certain activities and interact with the world around them is known as a disability. Despite the various efforts being done to ensure their rights and equity of the disabled, they still suffer more during various crises like conflicts, natural disasters and pandemics. The purpose of this narrative review is to access the impact that the COVID-19 pandemic has had on People with disability (PWD). For writing this narrative review, Google, Google Scholar, Pub Med and online news portals were searched by using various combination of the following terminologies; “Disability”, “Differently “Disabled”, “Disable”, “People with Disability”, “PWD” “Impact”, “COVID-19”, “Corona Pandemic”, “Challenges”, “Issues”, “Policies”, “Social”, and “increased risk”. The pandemic has created many challenges for people with disability. They not have greater risk of contracting COVID-19, but also have problems accessing health services. It has also had various social impacts like problems related to education, employment as well as discrimination. The COVID pandemic has exposed gaps in the health system that make the poor, marginalized and disabled population more vulnerable to neglect and mistreatment. Proper implementation and monitoring of policies should be done to ensure that PWD feel included and respected. It is important to continually integrate PWD into the mainstream society while minimizing their risks of contracting COVID-19. The caretakers should use the necessary PPE when attending to their needs. DOI: https://doi.org/10.46405/ejms.v3i2.294